Skills of Media Marketing of the Public Relations Staff: (University of Baghdad as a Model) - Al-Khaqani, Hassan Abd Alhadi (ALBAHITH ALALAMI, 2012)
Departments and offices of public relations and media in any institution or company is the most important departments that reflect the results of their work negatively or positively on their reputation. This goes beyond the trust and credibility that its internal and external audiences will give it. Where such matter requires the staff, working in these departments and offices, to have communication skills that qualify them to do the role of marketing the communication message. Yet, the communication skills of public relations and media staff vary from person to person depending on the communication position. This skill has two criteria: Achieving the communication goal and the speed in achieving it as a number of skills control some factors: Theoretical and innate preparations represented by the total personal, psychological, social and mental qualities acquired by the individual genetically and self-perception and mental abilities. An individual who is characterized by social intelligence and good linguistic ability can achieve successful communication with the institution’s internal and external audience. Hence, this research sheds light on the skills of media marketing for public relations staff. The researcher selected the Department of Media and Public Relations at the University of Baghdad as a model to survey the level of communication skills in marketing the media message when working in this theoretical field. The research consists of the methodological framework in terms of identifying and formulating the research problem; and the objective that this study aims to reach; as well as the two-part descriptive and analytical survey method adopted in this study. The researcher designed the questionnaire as a major tool for collecting information and data in order to achieve the objectives of the research to identify the level and types of media marketing skills possessed by public relations workers at the University of Baghdad. Whereas, the theoretical framework dealt with the first topic in the concept of communication and marketing skills, while the second section took care of the skills of media marketing. The field study included two axes: the first data of the respondents representing their characteristics in terms of sex, age, academic achievement, specialization and social status. The second investigates questions related to media marketing skills. Public relations staff resort to the media marketing of university messages, and the research has produced a number of important results.